2009
DOI: 10.3390/su1020215
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Systems Located in the Forest-Savanna Ecotone of the Venezuelan Amazonian. Are Organic Agroforestry Farms Sustainable?

Abstract: Abstract:The savannas located in the forest-savanna ecotone in the Venezuelan Amazon have unfertile sandy ultisols and entisols which show a very low crop production unless they are supplemented with large amounts of fertiliser. In spite of this restriction, local farmers have established long-term production systems by using low input doses of organic manure. The use of organic waste in unfertile ultisols and entisols typical of savannas have resulted in increases in organic matter content and biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…Preliminary results presented by López- showed that protection has also improved soil fertility, because of a reduction of compaction, an increase in the water holding capacity, organic matter, pH, exchangeable bases, organic phosphorus and total phosphorus and nitrogen. Microbial C-biomass for the EBLL savannas were higher than the values presented by Gómez et al (2008) and López-Hernández et al (2009) in Trachypogon savannas of Eastern Llanos and Venezuelan Amazonia, respectively. On the contrary, the dehydrogenase values although greater in PS respect NS were lower than the information reported by López-Gutiérrez et al (2004) and Gómez and Paolini (2011) in savannas of Eastern Llanos, Venezuela.…”
Section: Changes In Soil Physical Chemical and Biochemical Charactercontrasting
confidence: 69%
See 1 more Smart Citation
“…Preliminary results presented by López- showed that protection has also improved soil fertility, because of a reduction of compaction, an increase in the water holding capacity, organic matter, pH, exchangeable bases, organic phosphorus and total phosphorus and nitrogen. Microbial C-biomass for the EBLL savannas were higher than the values presented by Gómez et al (2008) and López-Hernández et al (2009) in Trachypogon savannas of Eastern Llanos and Venezuelan Amazonia, respectively. On the contrary, the dehydrogenase values although greater in PS respect NS were lower than the information reported by López-Gutiérrez et al (2004) and Gómez and Paolini (2011) in savannas of Eastern Llanos, Venezuela.…”
Section: Changes In Soil Physical Chemical and Biochemical Charactercontrasting
confidence: 69%
“…Moreover, earthworms are ascribed to affect soil fertility and plant growth through the production of casts which affects the availability and nature of both the spatial and trophic resource in soil. The beneficial effects of the earthworm activities include: i) improvement of soil physical properties which affect soil water retention capacity, drainage, and the formation and degradation of aggregates (Blanchart et al, 1999); ii) chemical and biological effects on the rate of organic matter degradation and nutrient cycling (Chapuis-Lardy et al, 2011;Lavelle et al, 1994;López-Hernández et al, 2004, 2009, and iii) alteration of the composition and activity of microorganisms and soil invertebrates (Lavelle and Spain, 2001). All these processes significantly impact the soil fertility primarily through the release of available forms of nitrogen (N) and phosphorus (P) (Baker, 2007;Chapuis-Lardy et al, 2011;Chaoui et al, 2003;Jiménez et al, 2003;López-Hernández et al, 1993) once the soil passes through the gut of the individual earthworm.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial and enzymatic activities in the organic agricultural forestry system (OAFS) and the natural savanna (NS) in Amazonas State, Venezuela. Modified from López-Hernández [33]. Microbial N-biomass also significantly increased after compost amendment, since both increment were of a similar magnitude the C-microbial biomass/N-microbial biomass was similar in NS and OAFS (Table 3).…”
Section: Age Distributionmentioning
confidence: 88%
“…Methodological aspects concerning earthworm collection and other soil quality indices of the Case Studies of the present revision have been already presented by López-Hernández and collaborators [5,6,12,13,33].…”
Section: Supporting Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation